Beyond Adherence: The Healthwork of People Living with HIV in Nigeria. Issue 1 (2nd January 2022) - Ogunrotifa, Ayodeji B.
ABSTRACT: Following the introduction of highly active antiretroviral therapy (HAART) in 1996, adherence was regarded by biomedical researchers as the only way to manage HIV effectively in everyday life. The sociological critique of this biomedical stance posits that the everyday management of HIV goes beyond the biomedical conception of adherence, as HIV-positive individuals undertake healthwork practices that form the basis of HIV management. Using symbolic interactionism and social context theory to ground the lived experience of healthwork, this paper explores the kinds of healthwork people living with HIV in Nigeria undertake. Drawing from 32 semi-structured interviews with HIV-positive individuals living in Nigeria, it was observed that healthwork is an individualized practice including spirituality, testing, counseling, adherence, concealment, dieting, and support-group participation. These practices are shaped by the sociocultural, economic, political, and structural factors in the Nigerian context. Meaningful healthwork practices were informed by the personal responses to HIV diagnosis, and such practices were tied to formal rules, local dynamics, and contextual issues that are shaped by structural and institutional factors. This paper contributes to sociological knowledge on HIV management by demonstrating the importance of context and meaning in the design of health interventions and programs connected with the lived experience of people living with HIV.